High-tech trash : glitch, noise, and aesthetic failure - Kane, Carolyn L. (Rhetoric and public culture (Oakland, Calif.) ;, 2019)
"High-Tech Trash: Glitch, Noise, and Aesthetic Failure maps an archaeology of failure in a culture seemingly ill-equipped to deal with it. To better understand failure, Kane argues, we must abstract from our subjective, personal disappointments and see them as meaningful symbols of a broader human struggle. By connecting twenty-first century digital aesthetics to critical issues in the history of high-tech, the book elucidates what it means to be an error-prone, fallible human in an age of hyper technology; to fail again and again without recourse to anything but repetition"--Provided by publisher.